French Multidisciplinary Approach for the Treatment of MSK Tumors - Cazzato, Roberto Luigi; Garnon, Julien; De Marini, Pierre; Auloge, Pierre; Dalili, Danoob; Koch, Guillaume; Antoni, Delphine; Barthelemy, Philippe; Kurtz, Jean Emmanuel; Malouf, Gabriel; Feydy, Antoine; Charles, Yan-Philippe; Gangi, Afshin (Seminars in Musculoskeletal Radiology, 2020)
Several interventional treatments have recently been integrated into the therapeutic armamentarium available for the treatment of bone tumors. In some scenarios (e.g., osteoid osteoma), interventional treatments represent the sole and definitive applied treatment. Due to the absence of widely shared protocols and the complex multivariate scenarios underlying the clinical presentation of the remaining bone tumors including metastases, therapeutic strategies derived from a multidisciplinary tumor board are essential to provide effective treatments tailored to each patient. In the present review, we present the multidisciplinary therapeutic strategies commonly adopted for the most frequent bone tumors.
Keywords: bone neoplasms; surgery; radiotherapy; medical oncology; radiology; Interventional